Unraveling the Role of Allo-Antibodies and Transplant Injury - Matsuda, Yoshiko; Sarwal, Minnie M. (Frontiers in Immunology, 2016)
Alloimmunity driving rejection in the context of solid organ transplantation can be grossly divided into mechanisms predominantly driven by either T cell-mediated rejection (TCMR) or antibody-mediated rejection (ABMR), though the co-existence of both types of rejections can be seen in a variable number of sampled grafts. Acute TCMR can generally be well controlled by the establishment of effective immunosuppression [1, 2]. Acute ABMR is a low frequency finding in the current era of blood group and HLA donor/recipient matching and the avoidance of engraftment in the context of high-titer, pre-formed donor specific antibodies. However, chronic ABMR remains a major complication resulting in the untimely loss of transplanted organs [3-10]. The close relationship between donor-specific antibodies (DSAs) and ABMR has been revealed by the highly sensitive detection of human leukocyte antigen (HLA) antibodies [11-16]. Injury to transplanted organs by activation of humoral immune reaction in the context of HLA identical transplants and the absence of donor specific antibodies (DSAs), strongly suggest the participation of non HLA (nHLA) antibodies in ABMR (17-25). In this review, we discuss the genesis of ABMR in the context of HLA and nHLA antibodies and summarize strategies for ABMR management.